Shariah: An efficiency analysis - Modack, Raeez Ahmed (School of Economics, 2022)
The oil shock of 1973 brought newfound wealth to a group of ultraconservative Muslims. This wealth coincided with the growing demand for shariah compliant products. The prohibition against interest is not new but has been around for millennia. This dissertation attempted to ascertain if Shariah compliance came at a cost to investors and if it was possible to be both just and efficient. We illustrate using Stiglitz and Cheung's sharecropping models that a profit and loss sharing contract can be as efficient as its alternatives (or more so), so there is no implicit tax on lenders who prefer a share of profit rather than a fixed return on a loan. The growth in Islamic finance has improved consumer awareness not only amongst Islamic investors, but also among ethical investors. Investors are now offered a chance to gain returns, without having to sacrifice their beliefs. Islamic finance may suffer from learning effects, portfolio managers certainly ‘learn by doing'. But once they have learned it seems that their portfolios need not underperform the market. However, it must be recognized that a lack of standardization and diverse scholar opinions can adversely affect the growth of the industry.